Use of microorganisms in the removal of pollutants from the wastewater - Colica, Giovanni (Premio Tesi di Dottorato, 2009)
The aims of this thesis were to test the adsorption efficiency of cyanobacterial biomasses of polysaccharide producing strains and to realize a pilot plant for galvanic waste treatment based on biosorption. First of all the different strains were tested at laboratory scale with solutions containing one or more metals, in order to gradually approach the reality of galvanic industries, where several metals at different concentrations are present at the same time in the wastes. To realize the pilot plant we tried to combine the protocols established during laboratory experiments with the necessities of the final user, the industry, by designing and realizing three prototypes. It was moreover evaluated the possibility to recover the adsorbed metal in a form easy and convenient for recycling.